A Combined Approach to Incremental Reasoning for EL Ontologies - Ren, Yuan; Pan, Jeff Z.; Guclu, Isa; Kollingbaum, Martin (Web Reasoning and Rule Systems, 2016)
Due to the dynamic nature of knowledge and data in semantic applications, ontology incremental reasoning technologies are essential for ontology management systems. Nowadays, many proposed incremental reasoning solutions and implemented systems apply forward chaining completion algorithms to handle the removal and addition of axioms. In this paper, we propose a novel approach to ontology incremental reasoning that combines forward and backward chaining completion for $$\mathcal {EL}$$ . Compared to existing work, this approach can be applied with or without bookkeeping, does not affect parallelisation or tractability, and reduces the effort for re-deriving the over-deleted results both theoretically and empirically.